Exploring physical education teachers’ experiences with incorporating technology into instruction - Culajara, Carla Jobelle; Dizon, John Loui; Lao, Anabella; Bandoy, Delverden (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
Keeping up with evolving concepts and teaching new knowledge require individuals to adapt to 21st century abilities in order to be future-ready and versatile in keeping up with the trends of an ever-changing educational landscape. Technology integration is a huge assist in offering meaningful and creative quality education services. The purpose of this study is to acquire an in-depth undertanding of physical education teachers' experiences with integrating ICT into lesson delivery. The study utilized qualitative study which employs a phenomenological approach. Purposive sampling was utilized in the study to fulfill the study's purpose of answering research concerns where 7 physical education teachers participated the study. Codes and themes were used in the study. Three themes emerged in the study: dynamic teaching and learning experiences, lack of access, and health problems. This study intends to highlight the significance of adopting and integrating technology into the current teaching and learning process, which highlights the significance of teaching of physical education teachers’ with showcasing the technical capabilities and skills. Additionally, by incorporating ICT, the study will highlight its beneficial outcomes and serves as a strategy will be developed to deal with the difficulties instructors have faced by creating policies for improving teachers’ technological skills as a result of these difficulties. The use of ICT to give instruction in physical education classes will highlight the study's beneficial effects. Every physical education teacher who uses ICT to give lessons in concepts, principles, and teaching and learning will benefit from the clarity this study will bring.